The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/(sici)1096-8628(19990219)82:5<385::aid-ajmg6>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of infantile free sialic acid storage disease

Abstract: Infantile free sialic acid storage disease (ISSD) is a rare autosomal recessive metabolic disorder caused by a lysosomal membrane transport defect, resulting in accumulation of free sialic acid within lysosomes. Only a few cases have been described. We report on three new cases of ISSD with different modes of presentation: an infant with nephrotic syndrome, a case of fetal and neonatal ascites with heart failure, and a case of fetal ascites with esophageal atresia type III. From these patients and a review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 26 publications
(44 reference statements)
1
26
0
Order By: Relevance
“…Determining whether this is the case will require analysis of a larger ethnic cohort and/or use of SNP-based linkage disequilibrium methods, beyond the scope of this report. The distribution of the observed storage material in our patients is similar to that reported previously (Lemyre et al 1999), and corresponds in a general sense to the expression pattern of sialin in the mouse (Yarovaya et al 2005).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Determining whether this is the case will require analysis of a larger ethnic cohort and/or use of SNP-based linkage disequilibrium methods, beyond the scope of this report. The distribution of the observed storage material in our patients is similar to that reported previously (Lemyre et al 1999), and corresponds in a general sense to the expression pattern of sialin in the mouse (Yarovaya et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…We are aware of one earlier report of two children with free sialic acid storage and increased neuraminidase activity in lymphocytes, although activity was normal in fibroblasts in these same patients (Ylitalo et al 1986). In contrast, several authors have reported neuraminidase activity in ISSD patients as "normal" or "not decreased" (Baumk€ otter et al 1985;Paschke et al 1986;Pueschel et al 1988;Fois et al 1987;Nakano et al 1996;Lemyre et al 1999). Whether this apparent inconsistency represents true biological variation, differences in technique, or a chance observation due to the influence of other genetic modifiers is unclear at present.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a mild type of lysosomal free sialic acid storage, i.e., Salla disease common in Finland, newborns develop intellectual impairment gradually. In the more severe allelic variant, i.e., infantile free sialic acid storage disease (ISSD), patients generally die early in childhood or even in utero [2]. Individuals with symptoms of moderate severity are considered to have "intermediate severe Salla disease."…”
Section: Introductionmentioning
confidence: 99%
“…However, Lemyre et al (1999) showed that a nephrotic syndrome occurred in four of seven ISSD patients in whom renal evaluation was performed, and ISSD seems to be an important cause of nephrosis in infants with a storage disorder phenotype.…”
Section: Introductionmentioning
confidence: 99%